2022
DOI: 10.1111/aogs.14435
|View full text |Cite
|
Sign up to set email alerts
|

Extravillous trophoblast invasion and decidualization in cesarean scar pregnancies

Abstract: Introduction:The increasing cesarean section rate has led to an increase in the number of subsequent pregnancies resulting in a cesarean scar pregnancy. There appears to be preferential attachment of the blastocyst to the scar site, which may be associated with defective decidua in that region, resulting in abnormal implantation, which can in turn negatively affect the success of the pregnancy. The aim of the current study was to evaluate the extravillous trophoblast, decidua, and myometrium in scar and adjace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Our study confirmed this hypothesis by indicating that chorionic villus thickness at the scar is a significant risk factor for failure of TAUS‐guided suction curettage alone of CSP; when the chorionic villus thickness at the scar exceeds 4.7 mm, the likelihood of failure increases by 15‐fold. This phenomenon may be attributed to the invasive nature of chorionic cells during early pregnancy, which preferentially adhere to and invade the scar area compared with the metaplastic area 25,26 . The aforementioned observation implies that the thickness of the chorionic villi at the scar may serve as an indicator of the extent of villi invasion, whereby a thicker chorionic villi layer corresponds to a higher degree of invasion and a greater probability of unsuccessful TAUS‐guided suction curettage.…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirmed this hypothesis by indicating that chorionic villus thickness at the scar is a significant risk factor for failure of TAUS‐guided suction curettage alone of CSP; when the chorionic villus thickness at the scar exceeds 4.7 mm, the likelihood of failure increases by 15‐fold. This phenomenon may be attributed to the invasive nature of chorionic cells during early pregnancy, which preferentially adhere to and invade the scar area compared with the metaplastic area 25,26 . The aforementioned observation implies that the thickness of the chorionic villi at the scar may serve as an indicator of the extent of villi invasion, whereby a thicker chorionic villi layer corresponds to a higher degree of invasion and a greater probability of unsuccessful TAUS‐guided suction curettage.…”
Section: Discussionmentioning
confidence: 99%
“…The process of uterine tissue repair after CS is often accompanied by decreasing endometrial glands, inhibition of myometrial smooth muscle cell growth, excessive collagen fiber deposition, and massive leukocyte infiltration, which leads to long-term and chronic inflammation and scarring ( 63 ). There appears to be preferential attachment of the blastocyst to the scar site, which may be associated with defective decidua in that region, resulting in abnormal implantation ( 64 ). In turn, disorientation of the implanted embryo and restricted stromal cell proliferation could also lead to defective decidualization and abnormal placental development, including excessive invasion of trophoblasts into the decidua and insufficient branching of fetal blood vessels ( 65 , 66 ).…”
Section: Approaches To Establish the Pas Modelmentioning
confidence: 99%
“…However, the mechanism and signaling pathway of how myometrial injury affects EVT invasion and placental development is rarely reported. Only a few studies have reported that EVT migration and invasion into the myometrium may be related to the downregulation of functional E-cadherin in the myometrium of uterine scars ( 64 ). This model is very suitable for research on the pathomechanism of PAS in the aspect of impaired myometrium.…”
Section: Approaches To Establish the Pas Modelmentioning
confidence: 99%
“…Serial sections (4 µm) were also prepared for Masson's trichrome (Masson), Alcian blue-periodic acid Schiff (AB-PAS) and immunohistochemistry staining. Masson and immunohistochemistry staining were performed according to the protocols established in Department of Pathology, Jinan University School of Medicine previously ( 6 ). The following primary antibodies were used: cluster of differentiation (CD)10 (cat.…”
Section: Case Reportmentioning
confidence: 99%